2019
DOI: 10.3390/healthcare7020070
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Borrelia burgdorferi and Helicobacter pylori Biofilms in Morgellons Disease Dermatological Specimens

Abstract: Background: Morgellons disease (MD) is a dermopathy that is associated with tick-borne illness. It is characterized by spontaneously developing skin lesions containing embedded or projecting filaments, and patients may also experience symptoms resembling those of Lyme disease (LD) including musculoskeletal, neurological and cardiovascular manifestations. Various species of Borrelia and co-infecting pathogens have been detected in body fluids and tissue specimens from MD patients. We sought to investigate the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…Recent studies linking Borrelia infection and MD provide evidence meeting many of the criteria proposed by Fredricks and Relman's molecular guidelines for establishing disease causation with sequence-based technology. 12,13,15,19 There are approximately 52 recorded species of Borrelia, of which 21 are classified into the LD group and 29 are classified into the RFB group (two species remain unclassified). Both Bb and RFB have been consistently detected in MD specimens.…”
Section: Infection Associated With MDmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies linking Borrelia infection and MD provide evidence meeting many of the criteria proposed by Fredricks and Relman's molecular guidelines for establishing disease causation with sequence-based technology. 12,13,15,19 There are approximately 52 recorded species of Borrelia, of which 21 are classified into the LD group and 29 are classified into the RFB group (two species remain unclassified). Both Bb and RFB have been consistently detected in MD specimens.…”
Section: Infection Associated With MDmentioning
confidence: 99%
“…15 Confocal microscopy of mixed aggregates revealed that Bb occupied the central portion of aggregates while Hp occupied the periphery, suggesting that they could have different functional roles, but also suggesting that Bb infection was established first followed by Hp infection. 15 In either case, the results suggest that mixed Borrelia biofilms may play a role in MD development and contribute towards Borrelia persistence and disease chronicity. Although the role of other pathogens and mixed infections in MD skin remains to be determined, it is possible that other microorganisms play a part in MD development and could be co-involved etiological factors in individual patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations